Chelate‐Thiolate‐Coordinate Ligands Modulating the Configuration and Electrochemical Property of Dinitrosyliron Complexes (DNICs). Issue 45 (25th September 2015) - Yeh, Shih‐Wey; Lin, Chih‐Wei; Liu, Bai‐Heng; Tsou, Chih‐Chin; Tsai, Ming‐Li; Liaw, Wen‐Feng
Abstract As opposed to the reversible redox reaction ({Fe(NO)2}10 reduced‐form DNIC [(NO)2Fe(S(CH2)3S)]2− (1)⇌{Fe(NO)2}9 oxidized‐form [(NO)2Fe(S(CH2)3S)]−), the chemical oxidation of the {Fe(NO)2}10 DNIC [(NO)2Fe(S(CH2)2S)]2− (2) generates the dinuclear {Fe(NO)2}9–{Fe(NO)2}9 complex [(NO)2Fe(μ‐SC2H4S)2Fe(NO)2]2− (3) bridged by two terminal [SC2H4S]2− ligands. On the basis of the Fe K‐edge pre‐edge energy and S K‐edge XAS, the oxidation of complex 1 yielding [(NO)2Fe(S(CH2)3S)]− is predominantly a metal‐based oxidation. The smaller S1‐Fe1‐S2 bond angle of 94.1(1)° observed in complex 1 (S1‐Fe1‐S2 88.6(1)° in complex 2), compared to the bigger bond angle of 100.9(1)° in the {Fe(NO)2}9 DNIC [(NO)2Fe(S(CH2)3S)]−, may be ascribed to the electron‐rich {Fe(NO)2}10 DNIC preferring a restricted bite angle to alleviate the electronic donation of the chelating thiolate to the electron‐rich {Fe(NO)2}10 core. The extended transition state and natural orbitals for chemical valence (ETS‐NOCV) analysis on the edt‐/pdt‐chelated {Fe(NO)2}9 and {Fe(NO)2}10 DNICs demonstrates how two key bonding interactions, that is, a FeS covalent σ bond and thiolate to the Fe d<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgkwbw5t1s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> z 2</alternatives> charge donation, between the chelating thiolate ligand and the {Fe(NO)2}9/10 core could be modulated by the backbone lengths of the chelating thiolate ligands to tune the electrochemical redox potential (E1/2=−1.64 V for complex 1 and E1/2=−1.33 V for complex 2) and to dictate structural rearrangement/chemical transformations (S‐Fe‐S bite angle and monomeric vs. dimeric DNICs).